Blue tales of a blue-tailed lizard: ecological correlates of tail autotomy in Micrablepharus atticolus (Squamata, Gymnophthalmidae) in a Neotropical savannah - Sousa, H. C.; Costa, B. M.; Morais, C. J. S.; Pantoja, D. L.; de Queiroz, T. A.; Vieira, C. R.; Colli, G. R. (Journal of zoology (1987), 2016)
Tail autotomy and regeneration are perhaps the most dramatic adaptations to enhance survival among lizards. In spite of much work on the subject, the ecological significance of tail autotomy rates in natural populations remains elusive, due to difficulties in controlling several confounding factors and the paucity of accurate demographic data. On the basis of a capture–recapture study, we investigate the ecological determinants of tail autotomy rates in Micrablepharus atticolus, a blue‐tailed lizard from the South American Cerrado. We tested whether habitat (as a proxy of predation intensity), seasonality (as a proxy of intensity of social interactions), ontogeny and sex affected autotomy rates, and also whether autotomy rates affected body condition. We found that tail autotomy rates in M. atticolus are lower than in many other species with brightly colored tails, likely resulting from a small body size and fossorial habits. Autotomy rates were lower than expected by chance in the plot with lower mortality rates, suggesting a more prominent role of predation intensity instead of predator efficiency, and increased with age, suggesting cumulative effects of predation attempts along the ontogeny or age‐specific differences in predation intensity. We also found no intersexual differences or any effect of breeding activity on autotomy rates. Our results indicate that energetic costs of tail autotomy are low, or that animals compensate tail loss with increased foraging rates. These characteristics of M. atticolus seem tightly associated with its small body size, fossorial lifestyle and very short life span, and suggest that the costs of tail regeneration should be low. The lizard Micrablepharus atticolus, endemic to the Brazilian Cerrado, sheds its brightly blue tail to evade predator attacks, a dramatic adaptation to enhance survival. Long‐term capture‐recapture data indicates that tail autotomy rates in M. atticolus are lower than in many other species with brightly colored tails. Further, rates of tail autotomy covaried with mortality rates, suggesting a more prominent role of predation intensity than predator efficiency, and increased with age, suggesting cumulative effects of predation attempts along the ontogeny. There were no intersexual differences or any effect of breeding activity on autotomy rates. Surprisingly, the energetic costs of tail autotomy were low and individuals compensate tail loss with increased foraging rates. This suite of traits seems tightly associated with M. atticolus small body size, fossorial lifestyle and very short life span.